PELAFALAN DAN PENGENALAN KOSAKATA PADA PEMELAJAR BIPA DI DALAM TES KEMAHIRAN BERBICARA - Rosida Erowati; Neneng Nurjanah (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2020)
Abstract: The speaking skills of BIPA 1 learners include the ability to pronounce Indonesian phonemes accurately. The accuracy of phoneme pronunciation is not only intended for fluency in speaking, but so that students are able to distinguish the meaning of words. By utilizing a qualitative descriptive approach, this study aims to describe the pronunciation of BIPA learners in Egypt in a speaking ability test. This pronunciation description indicates the ability of BIPA learners to recognize vocabulary, the meaning of words, as well as the difficulty of pronunciation in tests of speaking ability. The results of this study indicate that beginner BIPA learners in Egypt have difficulty at the phonological level, namely the phonetic articulation of consonant sounds / b /, / p /, / ŋ /, / ɲ /, / k /, / ʔ / and consistently having difficulty to map sound / b / to / p /. In addition, it tends to double the sound / ŋ / with / ɡ /, also avoiding the sound / ɲ /.Abstrak: Kemahiran berbicara pemelajar BIPA 1 mencakup kemampuan melafalkan fonem bahasa Indonesia dengan jitu. Ketepatan pelafalan fonem tidak semata ditujukan untuk kelancaran berbicara, namun agar pemelajar mampu membedakan makna kata. Dengan memanfaatkan pendekatan deskriptif kualitatif, penelitian ini bertujuan mendeskripsikan pelafalan pemelajar BIPA di Mesir dalam tes kemampuan berbicara. Deskripsi pelafalan ini mengindikasikan kemampuan pemelajar BIPA dalam mengenali kosakata, makna kata-kata, serta kesulitan pelafalan dalam tes kemampuan berbicara. Hasil penelitian ini menunjukkan bahwa pemelajar BIPA pemula di Mesir memiliki kesulitan pada level fonologis, yaitu pada artikulasi fonetik pada bunyi konsonan /b/, /p/, /ŋ/, /ɲ/, /k/, /ʔ/ dan secara konsisten kesulitan untuk memetakan bunyi /b/ ke /p/. Selain itu, cenderung menggandakan bunyi /ŋ/ dengan /ɡ/, juga menghindari bunyi /ɲ/.